2015
DOI: 10.1038/gt.2015.14
|View full text |Cite
|
Sign up to set email alerts
|

The role of transduced bone marrow cells overexpressing BMP-2 in healing critical-sized defects in a mouse femur

Abstract: The role that transduced mouse bone marrow stromal cells (mBMSCs) engineered to overexpress human bone morphogenetic protein 2 (BMP-2) play in healing critical-sized skeletal defects is largely unknown. We evaluated the interaction between host osteoprogenitor cells and donor mBMSCs transduced with either a lentiviral (LV) vector-expressing red fluorescent protein (RFP) with or without BMP-2 that were implanted into a critical-sized femoral defect. Radiographs taken at the time of killing were evaluated using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…We first observed that scAAV‐equine‐BMP‐2 transduced cells produced significantly more BMP‐2 protein than any other treatment group (Figure ). This is in agreement with several other groups utilizing a traditional ex vivo transduction technique . Importantly, the one‐time scAAV‐equine‐BMP‐2 transduction produced significantly more protein than what is clinically available today without repeat administration of rhBMP‐2.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We first observed that scAAV‐equine‐BMP‐2 transduced cells produced significantly more BMP‐2 protein than any other treatment group (Figure ). This is in agreement with several other groups utilizing a traditional ex vivo transduction technique . Importantly, the one‐time scAAV‐equine‐BMP‐2 transduction produced significantly more protein than what is clinically available today without repeat administration of rhBMP‐2.…”
Section: Discussionsupporting
confidence: 89%
“…This is in agreement with several other groups utilizing a traditional ex vivo transduction technique. 33,34 Importantly, the one-time scAAV-equine-BMP-2 transduction produced significantly more protein than what is clinically available today without repeat administration of rhBMP-2. While this study did not incorporate the use of a carrier, protein elution from genetically modified cells loaded onto a carrier would be expected to remain unchanged, and protein delivery would then be dependent on cell delivery, and not dictated by hydrolysis and elution characteristics of various scaffolds.…”
Section: Discussionmentioning
confidence: 99%
“…This supports the idea that host cells, even in non-regenerative contexts, can be induced to regenerate and also suggests that engineered cells, with their enhanced communications, could be a suitable medium to overcome the block to regeneration. In another example, mesenchymal stem cells were engineered to overexpress the growth factor BMP-2 to increase bone regeneration responses [39]. These studies represent validation of the idea that engineered cells can be used as the basis for regenerative therapeutic interventions, and lays the foundation for more complex and rational interventions.…”
Section: Engineering Regeneration In Non-regenerating Systemsmentioning
confidence: 99%
“…A biomimetic periosteum can maintain homeostasis of the cellular microenvironment by delivering growth factors. A previous study showed that paracrine factors of MSCs play a positive role in bone repair [23, 24]. During bone healing, the proliferation and osteoblastic differentiation of endogenous or exogenous MSCs are influenced by various growth factors, among which TGF- β and BMPs play a major role.…”
Section: Discussionmentioning
confidence: 99%